ANALYSIS AND SYNTHESIS IN AVIATION TRIBOLOGICAL SYSTEMS - Kindrachuk, Myroslav; Kornienko, Anatolii; Stebeletska, Nataliia; Humenyuk, Ihor; Kharchenko, Volodymyr; Hlovyn, Andrii; Fedorchuk, Svitlana (Problems of Friction and Wear, 2026)
This paper examines current issues in tribology within aviation systems in the context of improving technical safety and extending the service life of friction components. The limitations of traditional analytical methods in the study of complex open non-equilibrium systems are identified, and the feasibility of combining methods of analysis and synthesis to generalize multifactorial processes of friction, wear, and failure is substantiated. The formation of tribological contact at the microlevel is analyzed, where friction is considered as a result of the dynamics of interatomic bonds. The role of self-organization processes and the formation of tribostructures in ensuring steady-state operating modes of tribosystems is revealed. It is shown that the stability of such modes is determined by the dynamic equilibrium between energy and mass flows and the increase in entropy. The nature of gradual and sudden failures has been investigated, in particular the autocatalytic mechanisms of tribostructure destruction. The application of probabilistic methods, in particular Bayesian analysis, has been justified to improve the reliability of diagnosing the technical condition of friction units and assessing the risk of rare failures. The comprehensive use of synthesis methods, the development of intelligent diagnostic systems, and a deeper understanding of the internal structure of tribological processes are considered a priority direction for improving the reliability of aviation tribosystems.